Cultural Representation in Grade 1 Reading Books in Schools in the Western Cape of South Africa - Nathalie Cupido; Candice Livingston (Universitas Negeri Semarang, 2024)
This study examines how African narratives and identities are represented in Grade 1 reading books from two Cape Winelands schools, evaluating the impact of post-Apartheid educational reforms on inclusivity and cultural relevance. Through qualitative content analysis, Afrikaans and isiXhosa materials are compared, focusing on themes, characters, settings, and hidden messages. Findings indicate Afrikaan's books prioritize Eurocentric narratives with dominant white characters and Western settings, marginalizing South African cultural realities. IsiXhosa books include more culturally relevant content but retain traces of Western epistemology. The study highlights how hidden curricula reinforce social inequalities by privileging Western worldviews, undermining African learners' cultural identity and self-awareness. It advocates for Afrocentric children's literature integrating indigenous knowledge, fostering cultural appreciation and educational equity. Curriculum developers, teacher education programs, and schools should adopt inclusive, contextually relevant materials that reflect learners' lived experiences and support identity formation.